2010
DOI: 10.1186/1742-2094-7-86
|View full text |Cite
|
Sign up to set email alerts
|

Induction of heme oxygenase-1 attenuates lipopolysaccharide-induced cyclooxygenase-2 expression in mouse brain endothelial cells

Abstract: BackgroundProstaglandin E2 (PGE2), an arachidonic acid metabolite converted by cyclooxygenase-2 (COX-2), plays important roles in the regulation of endothelial functions in response to bacterial infection. The enzymatic activity of COX-2 can be down-regulated by heme oxygenase-1 (HO-1) induction. However, the mechanisms underlying HO-1 modulating COX-2 protein expression are not known.ObjectiveThe aim of the present study was to investigate whether the up-regulation of HO-1 regulates COX-2 expression induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 45 publications
5
40
0
Order By: Relevance
“…In addition, upregulation of HO-1 in activated macrophages suppressed expression of COX-2, which culminated in the reduction of PGE 2 synthesis [18,36,37]. In the present study, we found that expression levels of the COX-2 and IL-1b genes were significantly suppressed by pretreatment with 50 lM hemin when the HFLS cells were subjected to 10% mechanical stretch (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…In addition, upregulation of HO-1 in activated macrophages suppressed expression of COX-2, which culminated in the reduction of PGE 2 synthesis [18,36,37]. In the present study, we found that expression levels of the COX-2 and IL-1b genes were significantly suppressed by pretreatment with 50 lM hemin when the HFLS cells were subjected to 10% mechanical stretch (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…e l s e v i e r . c o m / l o c a t e / i n t i m p of proinflammatory mediators such as TNF-α, IL-1β, iNOS, COX-2, NO, and PGE 2 [11,12].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…In addition, HO-1 expression by CoPP exerts anti-inflammatory effects, including down-regulated proinflammatory cytokines and cytoprotective functions in acute lung injury followed by LPS challenge (55). Up-regulation of HO-1 by CoPP significantly inhibited LPS-induced iNOS and COX-2 expression and NO and PGE 2 production in RAW264.7 macrophages (56) and murine bEnd.3 cells (57).…”
Section: Total Nrf2mentioning
confidence: 99%